2016
DOI: 10.1111/tpj.13194
|View full text |Cite
|
Sign up to set email alerts
|

Solanum pennelliibackcross inbred lines (BILs) link small genomic bins with tomato traits

Abstract: SUMMARYWe present a resource for fine mapping of traits derived from the wild tomato species Solanum pennellii (LA0716). The population of backcross inbred lines (BILs) is composed of 446 lines derived after a few generations of backcrosses of the wild species with cultivated tomato (cultivar M82; LA3475), followed by more than seven generations of self-pollination. The BILs were genotyped using the 10K SOL-CAP single nucleotide polymorphism (SNP) -Chip, and 3700 polymorphic markers were used to map recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 43 publications
1
92
0
Order By: Relevance
“…We next sought to validate these putative canalization QTL by analyzing a subset of the independently derived S. pennellii backcrossed introgression lines (BILs) (Ofner et al, 2016), which provide increased resolution of the regions of interest. For this purpose, we focused on the putative canalized primary metabolite QTL on chromosome 10, specifically the hot spot in IL10-1, and were able to confirm 9 (out of 25) cmQTL mapped to chromosome 10, using the BIL population.…”
Section: Validation Of Identified Cmqtl With the Solanum Pennellii Bimentioning
confidence: 99%
See 1 more Smart Citation
“…We next sought to validate these putative canalization QTL by analyzing a subset of the independently derived S. pennellii backcrossed introgression lines (BILs) (Ofner et al, 2016), which provide increased resolution of the regions of interest. For this purpose, we focused on the putative canalized primary metabolite QTL on chromosome 10, specifically the hot spot in IL10-1, and were able to confirm 9 (out of 25) cmQTL mapped to chromosome 10, using the BIL population.…”
Section: Validation Of Identified Cmqtl With the Solanum Pennellii Bimentioning
confidence: 99%
“…Correlation analysis was also performed across the entire population by means of the Pearson correlation coefficient to determine possible technical artifacts. A gas chromatography-mass spectrometry analysis was also performed on fruit materials harvested in three independent field trials from selected Solanum pennellii BILs (Ofner et al 2016).…”
Section: Mqtl Mapping In the Il Populationmentioning
confidence: 99%
“…S. pennellii is a wild, green-fruited tomato species native to Peru that exhibits beneficial traits such as abiotic stress resistances (Lippman et al, 2007;Koenig et al, 2013). The previously sequenced accession LA716 (Bolger et al, 2014a) has been used to generate a panel of introgression (Eshed and Zamir, 1995) and backcrossed introgression (Ofner et al, 2016) lines that have been used to identify many interesting quantitative trait loci (Alseekh et al, 2015;Fernandez-Moreno et al, 2017), thus complementing large-scale genomic panel studies for tomato (Lin et al, 2014;Tieman et al, 2017). However, the accession LA716 does not perform well in the field and carries the NECROTIC DWARF gene on chromosome 6, which reduces plant vigor when introduced into a Solanum lycopersicum background (Ranjan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An additional two lines have overlapping introgressions on chromosome 1. The tentative conclusion that these overlapping regions contain the loci that confer susceptibility in S. pennellii , or resistance in S. lycopersicum , is supported by the observation that lines from the sub‐IL and BIL‐collections (Alseekh et al , Ofner et al ), which have introgressions in the overlap regions, are also susceptible (Table ).…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we describe the responses of different tomato lines to an infection by Cuscuta . Our host plant set included S. lycopersicum , S. pennellii , long‐established ILs derived from these two parental lines (Eshed and Zamir ) and selected sub‐ILs and BILs, which became available during the course of the study (Alseekh et al , Ofner et al ). In general, we found that the speed of infection of the tomato species was not as high as in the Cuscuta ‐ Pelargonium interaction, which has been characterized in detail (Johnsen et al , Olsen et al , Olsen and Krause ).…”
Section: Discussionmentioning
confidence: 99%